Promoting a private investment renaissance in Italy - Pisu, Mauro (OECD Economics Department Working Papers, 2017)
Boosting investment is key to supporting the nascent recovery and reviving stagnant productivity. Aggregate investment has declined markedly since the start of the global financial crisis, especially in services. Italy's investment is so low that the capital stock is now declining, hurting potential output growth. Raising investment will hinge on improving insolvency procedures, enhancing business dynamism, strengthening the innovation system and targeting incentives toward start-ups and innovative SMEs, overcoming problems in the banking sector and restarting lending to firms in addition to diversifying sources of firms' finance